A novel electrical charging condensing heat exchanger for efficient particle emission reduction in small wood boilers. (January 2020) - Grigonytė-Lopez Rodriguez, Julija; Suhonen, Heikki; Laitinen, Ari; Tissari, Jarkko; Kortelainen, Miika; Tiitta, Petri; Lähde, Anna; Keskinen, Jorma; Jokiniemi, Jorma; Sippula, Olli
Abstract: Small-scale biomass combustion is an important source of fine particles in ambient air, causing adverse health and environmental effects. Thus, there is a clear need to develop efficient and feasible flue gas cleaning technologies for small-scale combustion appliances. In this study a novel electrical charging condensing heat exchanger (eCHX) for combined fine particle removal and efficient heat recovery from flue gases was demonstrated in a small biomass-fired boiler. The method is based on the combination of a shielded corona charger and a condensing heat exchanger, where fine particles are removed by the electrophoretic, thermophoretic and diffusiophoretic forces. The eCHX was found to decrease >80% of fine particle mass (PM1 ) emissions and >40% of particle number emissions with simultaneous high thermal efficiency in the heat exchanger. The usage of the condensing heat exchanger without electrical charging resulted in 40% decrease in PM1 emissions when compared to the usage of a traditional tube heat exchanger. The advantage of the eCHX system is that it replaces the conventional heat exchanger in boilers, making it a compact and inexpensive solution, when compared to additional flue gas cleaning devices installed after the boiler. Graphical abstract: Image 1 Highlights: Small-scale wood combustion generates high PM1 concentration. High (>80%) PM1 reduction with novel electrical charging heat exchanger. PM1 reduction by the electrophoretic, thermophoretic and diffusiophoretic forces. Shielded corona charger as an alternative to electrostatic precipitator.